Desenvolvimento de programa computacional para dimensionamento de cristalizador ideal - Gois, Maria Beatriz de Mendonça (2020)
Crystallization of a system occurs when nucleation and crystal growth are benefited by the degree of supersaturation of the suspension. For this, the study of thermodynamics and crystallization kinetics are essential for the design of a crystallizer. However, the understanding of these two processes varies according to the system that will be used and, because of that, traditional simulation software sometimes has systems that are commonly used or sometimes has no previously implemented crystallizer model. Therefore, this work demonstrates how to use Excel, especially the intrinsic programming platform called Visual Basic For Applications (VBA), for the simulation and design of equipment in a versatile, effective and accessible way for Chemical Engineers. For this purpose, the report by Favier et al. (2016) was used, where the results served as a comparison for the information obtained with the developed program; and the crystallizer design process followed the levels defined by Lewis et al. (2015), which are: (i) initial design specifications, (ii) crystalline product design, (iii) crystallization physicochemical design, (iv) process flowsheet and (v) crystallizer design. The code implemented in VBA automated the execution of steps (iv) and (v). With that, it was possible to test different flow rates and design characteristics to achieve certain conditions and demands, obtaining an error of less than 0.5% when compared with the report issued by Favier et al. (2016).